Tamaño óptimo de la muestra (Optimum sample size) - Badii Zabeh, Mohammad Hosein; Castillo, J.; Guillén, A. (Facultad de Contaduría Pública y Administración U.A.N.L., 2008)
Abstract. The basics of sample size estimation process are described. Assuming the normal distribution, the procedures for estimation of sample size for the mean; with and without knowledge of the population variance, and population proportion are noted. Sample size for more than one population feature is also given.